Why Have the Swines not Devoured Him in His Swaddling Clothes? A Letter to His Son, Sent by Balcer Wilkowski (1584) - Buožytė, Eleonora (Literatūra, 2018)
[full article and abstract in Lithuanian; abstract in English] This paper gives a translation and analysis of the letter (1583) written by Balcer Wilkowski, a member of the Polish Brethren, to his son Kaspar, who was the physician of Mikołaj Krzysztof Radziwiłł the Orphan (1549–1616), as well as a renowned translator and polemist. In 1583, Kaspar Wilkowski left the Polish Brethren in Lublin and departed for Vilnius, where he published his Przyczyny nawrocenia do wiary powszechneyod sekt nowokrzczeńcow samosateńskich (“The Causes for the Conversion to the Universal Faith from the Samosatene Anabaptist Sects,” Vilnius, 1583). Contained in two volumes, this book provides an explanation for his turn to the Catholic Church. The same year, his father Balcer Wilkowski, in all probability without seeing the son’s book, wrote him a letter, asking Kaspar to return to the “true faith.” The letter was first published in 1584, as an annex to Jan Niemojewski’s (1526–1598) Vkazanie iż Koscioł Rzymski Papieski nie iestapostolski áni swięty, áni ieden, áni powszechny (“An Argument that the Roman Church is neither Apostolic, nor Holy, nor One, nor Universal,” Kraków, 1584). Using passages from the Scripture, Balcer warns his son that his turn to Catholicism will only end in his personal perdition. This egodocument demonstrates not only Balcer’s personal reaction to the apostasy of his son, but the reaction of the whole Polish Brethren in Lublin likewise. It proves to be a valuable historical source for the Wilkowski biographies and the studies of the Community, including their religious beliefs.